Análise dos determinantes da proficiência dos cursos de engenharia no ENADE 2011 e 2014 - Almeida, Nikael de Carvalho (2018)
The importance of innovation for the long-term growth of countries already integrated into long-standing debates of economic theory. Given that the human capital accumulation and angular part of this process, its index of determining factors can provide information on how to improve the dynamics. Thus, the present work aimed to analyze the determinants of the academic performance of the engineering courses in Brazil through the tests of ENADE. The results reveal a significant importance of factors such as family background and socioeconomic context on student proficiency. They also reveal an existence of a peer effect, that is, institutions with better collective outcomes associated with better individuals results.